2022
DOI: 10.2131/jts.47.349
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of UAF1 alleviates sevoflurane-induced cognitive impairment and neurotoxicity in rats by inhibiting pro-inflammatory signaling and oxidative stress

Abstract: Evidence has shown that suppression of the activation of NLRP3 inflammasome could ameliorate surgery/sevoflurane (SEV)-induced post-operative cognitive dysfunction (POCD). However, the underlying mechanisms remain unclear. UAF1 acts as a binding partner of USP1, which inhibits the ubiquitination-mediated degradation of NLRP3, indicating that UAF1 may be implicated in POCD through regulating the NLRP3 inflammasome. Here, we studied the role of UAF1/NLRP3 in SEV-induced cognitive impairment and neurotoxicity in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 37 publications
0
0
0
Order By: Relevance
“…This led to a downregulation of hippocampal NLRP3, IκBα, p65, and MDA expression, and an upregulation of SOD and CAT protein levels. As a result, hippocampal inflammation and OS were inhibited, which in turn alleviated cognitive impairment and neurotoxicity in the rats [ 90 ]. In a mouse model of oxygen–glucose deprivation/reperfusion (OGD/R)-induced myocardial I/R, pubescenoside A (PBA) demonstrated selective and covalent binding to the conserved cysteine (Cys) residues Cys77 and Cys434 of Keap1.…”
Section: Potential Mechanisms Of Nlrp3 Inflammasome Ubiquitination/ D...mentioning
confidence: 99%
“…This led to a downregulation of hippocampal NLRP3, IκBα, p65, and MDA expression, and an upregulation of SOD and CAT protein levels. As a result, hippocampal inflammation and OS were inhibited, which in turn alleviated cognitive impairment and neurotoxicity in the rats [ 90 ]. In a mouse model of oxygen–glucose deprivation/reperfusion (OGD/R)-induced myocardial I/R, pubescenoside A (PBA) demonstrated selective and covalent binding to the conserved cysteine (Cys) residues Cys77 and Cys434 of Keap1.…”
Section: Potential Mechanisms Of Nlrp3 Inflammasome Ubiquitination/ D...mentioning
confidence: 99%
“…In a neonatal rat experiment, Zhu et al 17 found that USP1-associated factor 1 inhibits the degradation of NOD-like receptor protein 3 through the ubiquitin-proteasome pathway, which can aggravate sevoflurane-induced POCD. Therefore, downregulation of USP1-associated factor 1 reduces cognitive impairment.…”
mentioning
confidence: 99%